Experimental investigation of phase relationship in Ti–Fe-Hf ternary system. (December 2019) - Hu, T.; Zeng, Y.; Huang, X.M.; Cai, G.M.; He, Y.H.; Jin, Z.P.
Abstract: Based on diffusion triple and equilibrated alloy methods, phase relations in the Ti–Fe-Hf ternary system were investigated using the experimental data obtained through the combination of optical microscopy (OM), X-ray diffraction (XRD), scanning electron microscopy (SEM), and electron probe microanalysis (EPMA) techniques. Isothermal sections of the Ti–Fe-Hf system at both 1073 K and 1273 K were well constructed. There are three and four three-phase regions in these two sections, respectively. According to the present results, Hf can dissolve into FeTi at approximately 3.0% at both 1073 K and 1273 K. A continuous solid solution of Fe2 (Ti, Hf) forms between the binary intermediate compounds Fe2 Ti and Fe2 Hf (h). Fe2 Hf(c) and FeHf2 show large solid solubilities. The solubility of Ti in Fe2 Hf(c) changes from 33.9% at 1073 K to 39.0% at 1273 K, while that of FeHf2 can reach up to approximately 63.0% at 1273 K. No ternary compound exists in the Ti–Fe-Hf ternary system. Highlights: The Ti–Fe-Hf ternary system were systematically investigated by diffusion triples and several key equilibrated alloys. 1073 and 1273 K isothermal sections of Ti–Fe-Hf system were established for the first time. The continuous solid solution Fe2 (Ti, Hf) exists in the 1073 K and 1273 K isothermal section. The solid solubility of Ti in FeHf2 phase was up to 56.4 at. % at 1073 K.